Iron metabolism in rheumatic diseases - Aliakbar Givian; Amin Azizan; Ahmadreza Jamshidi; Mahdi Mahmoudi; Elham Farhadi (Journal of Translational Autoimmunity)
Iron is a crucial element for living organism in terms of oxygen transport, hematopoiesis, enzymatic activity, mitochondrial respiratory chain function and also immune system function. The human being has evolved a mechanism to regulate body iron. In some rheumatic diseases such as rheumatoid arthritis (RA), systemic lupus erythematous (SLE), systemic sclerosis (SSc), ankylosing spondylitis (AS), and gout, this balanced iron regulation is impaired. Altered iron homeostasis can contribute to disease progression through ROS production, fibrosis, inflammation, abnormal bone homeostasis, NETosis and cell senescence. In this review, we have focused on the iron metabolism in rheumatic disease and its role in disease progression.